Pengaruh Tekanan Kompresi Terhadap Daya dan Torsi Pada Engine Single Piston - Purnomo, Bagiyo Condro; Munahar, Suroto (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2019)
LPG is an alternative fuel as fuel oil (BBM) which has a higher octane and energy value compared to BBM, and produces lower exhaust emissions. However, engine performance has decreased. This research presents an analysis of the performance of a single piston 4-stroke LPG engine with changes in compression pressure. Tests were carried out to determine the power and torque with variable pressure compression of Â 9 bar, 9.5 bar and 10 bar. The test results show that a single piston 4-stroke LPG engine with 9 Bar compression pressure produces a maximum torque of Â 9.77 Nm at 3380 rpm and a maximum power of 6.7 HP at 5870 rpm. Whereas the 10 Bar compression pressure produces a maximum torque value of 10.79 Nm at 3689 rpm and a maximum power of 6.9 hp at 5936 rpm. The conclusion of this research is that the higher the engine compression pressure, the higher the thermal efficiency in the combustion chamber so that engine performance increases